Effects of Volute Design and Number of Impeller Blades on Lateral Impeller Forces and Hydraulic Performance - Daniel O. Baun; Ronald D. Flack (International Journal of Rotating Machinery)
A comparison is made between the characteristics of the measured lateral impeller forces and the hydraulic performances of a four- and a five-vane impeller, each operating in a spiral volute, a concentric volute, and a double volute. The pump's rotor was supported in magnetic bearings. In addition to supporting and controlling the rotor motion, the magnetic bearings also served as active load cells and were used to measure the impeller forces acting on the pump's rotor. The lateral impeller force characteristics, as a function of a normalized flow coefficient, were virtually identical in the four- and five-vane impellers in each respective volute type. The measured impeller forces for each volute type were compared with correlations in the literature. The measured forces from the double volute configurations agreed with the forces from a correlation model over the full flow range. Single volute configurations compared well with the predictions of a published correlation at high flow rates, ϕ/ϕn>0.5. Concentric volute configurations compared well with a published correlation at low flow rates, ϕ/ϕn<0.4. The head-versus-flow characteristics of the four-vane impeller in each volute type were stable over a greater flow range than the corresponding characteristics of the five-vane impeller. At higher flow rates in the stable region of the head's characteristic curves near the best efficiency point, the five-vane impeller produced higher head than did the four-vane impeller in each volute type.